2014
DOI: 10.1038/eye.2014.234
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of orthoptists to give intravitreal injections—a multidisciplinary approach

Abstract: Sir, Utilisation of orthoptists to give intravitreal injections-a multidisciplinary approachWe read with interest the study conducted by the Medical Retina Intravitreal (IVT) Service at Moorfields Eye Hospital reporting the use of nurses to give IVT injections, and wish to report the utilisation of orthoptists at Frimley Park Hospital (FPH) and Oxford Eye Hospital (OEH) to deliver injections as part of their macular services. 1 With the exponential growth in numbers of patients requiring IVT injections of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…Notwithstanding this, to address significant workload on ophthalmology clinics, allied healthcare professional (AHP)-led intravitreal injection clinics have been established by multiple HES centres. Ophthalmic nurse practitioners, hospital optometrists, technicians and orthoptists play an increasingly significant role in the delivery of routine retina care, with extended roles helping to expand service provision capacity [35–37]. Results show positive patient satisfaction with a nurse-led injection service, with little variation in patient experience when compared to a doctor-led service, and an acceptable safety profile [35, 38].…”
Section: Practices For Managing Capacity Issues To Meet Current and Fmentioning
confidence: 99%
“…Notwithstanding this, to address significant workload on ophthalmology clinics, allied healthcare professional (AHP)-led intravitreal injection clinics have been established by multiple HES centres. Ophthalmic nurse practitioners, hospital optometrists, technicians and orthoptists play an increasingly significant role in the delivery of routine retina care, with extended roles helping to expand service provision capacity [35–37]. Results show positive patient satisfaction with a nurse-led injection service, with little variation in patient experience when compared to a doctor-led service, and an acceptable safety profile [35, 38].…”
Section: Practices For Managing Capacity Issues To Meet Current and Fmentioning
confidence: 99%
“…However, in the letter from Mall et al, 1 there appeared to be no reference to medico-legal consultation on this new scope of professional practice for orthoptists.…”
Section: Sir Indemnity For Orthoptist-delivered Intravitreal Injectionsmentioning
confidence: 99%
“…We read with interest the article 'Fellow eye effect of unilateral intravitreal bevacizumab injection in eyes with diabetic macular edema'. 1 The authors report improvement in the non-injected eye of patients that received unilateral bevacizumab for diabetic macular oedema. A previous study also reported a significant difference in the mean macular thickness of the fellow eye treated with unilateral intravitreal bevacizumab for diabetic macular oedema, but no difference in the fellow eye of those receiving unilateral ranibizumab.…”
Section: Sir Indemnity For Orthoptist-delivered Intravitreal Injectionsmentioning
confidence: 99%
See 2 more Smart Citations